1999
DOI: 10.1038/sj.bjc.6690800
|View full text |Cite
|
Sign up to set email alerts
|

Phase I clinical study applying autologous immunological effector cells transfected with the interleukin-2 gene in patients with metastatic renal cancer, colorectal cancer and lymphoma

Abstract: Summary Natural killer-like T lymphocytes termed cytokine-induced killer (CIK) cells have been shown to eradicate established tumours in a severe combined immune deficient (SCID) mouse/human lymphoma model. Recently, we demonstrated that CIK cells transfected with cytokine genes possess an improved proliferation rate and a significantly higher cytotoxic activity as compared to non-transfected cells. Here, in a phase I clinical protocol, autologous CIK cells were generated from peripheral blood obtained by leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
129
1
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(134 citation statements)
references
References 22 publications
1
129
1
3
Order By: Relevance
“…IL2 is mainly produced by T cells during their activation and enhances their own expansion. 20,21 Production of IL2 is diminished in many patients with cancer due to T cell anergy [45][46][47] and several phase I studies [23][24][25][26]48 have shown that administration of Ad5-IL2 gene-modified tumor cells can induce specific antitumor responses mediated by T cells. Although successful in these studies in solid tumors, Ad5-IL2 is limited in gene therapy of hematopoietic malignancies by its low efficacy of infection and by a high toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…IL2 is mainly produced by T cells during their activation and enhances their own expansion. 20,21 Production of IL2 is diminished in many patients with cancer due to T cell anergy [45][46][47] and several phase I studies [23][24][25][26]48 have shown that administration of Ad5-IL2 gene-modified tumor cells can induce specific antitumor responses mediated by T cells. Although successful in these studies in solid tumors, Ad5-IL2 is limited in gene therapy of hematopoietic malignancies by its low efficacy of infection and by a high toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…NK -like T cells are established effector cells with clinical relevance. 21 Many tumors do not elicit an antigen-specific T-cell response, which may be due to the absence of functional DCs or failure of induction of effector cells in patients with tumor. 2 Recently, DCs have been used in several studies to increase the cytotoxic activity of immunologic effector cells in vitro or in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies [20,21] have illuminated that CIK possessed much stronger cytotoxicity than LAK to several kinds of cancer such as leukemia, renal cell carcinoma, melanoma [22] , and proved that dendritic cells increased in serum of host after transfusion of CIK to HCC patients. Here we demonstrated CIK cells from HCC patients could equally kill drug-resistant HCC cell line as those from normal.…”
Section: Discussionmentioning
confidence: 99%
“…A triplicate of same samples was placed to control variation. Cells were incubated at 37 ℃ with 50 mL/L CO 2 for 48 h prior to the addition of 10 L of MTT [18,20] (5 g/L, Sigma). After another 4 h of incubation, the plate was centrifuged at 3 000 r/min for 5 min, medium was discarded, 150 L of DMSO was added to each well.…”
Section: Drug-resistance Testmentioning
confidence: 99%